Identification of novel GAPDH-derived antimicrobial peptides secreted by Saccharomyces cerevisiae and involved in wine microbial interactions - Branco, Patrícia (2017)
Submitted by Paula Saraiva (psaraiva@egasmoniz.edu.pt) on 2017-05-30T15:29:02Z No. of bitstreams: 1 Artigo_04_GAlmeida.pdf: 742038 bytes, checksum: e1d3984db73f0991938fa91bfe5e1edc (MD5)